How does financial globalization affect risk sharing? Patterns and channels - M. Ayhan Kose; Eswar S. Prasad; Marco E. Terrones (Institute for the Study of Labor (IZA), 2007)
In theory, one of the main benefits of financial globalization is that it should allow for more efficient international risk sharing. In this paper, we provide a comprehensive empirical evaluation of the patterns of risk sharing among different groups of countries and examine how international financial integration has affected the evolution of risk sharing patterns. Using a variety of empirical techniques, we conclude that there is at best a modest degree of international risk sharing, and certainly nowhere near the levels predicted by theory. In addition, only industrial countries have attained better risk sharing outcomes during the recent period of globalization. Developing countries have, by and large, been shut out of this benefit. The most interesting result is that even emerging market economies, which have witnessed large increases in cross-border capital flows, have seen little change in their ability to share risk. We find that the composition of flows may help explain why emerging markets have not been able to realize this presumed benefit of financial globalization. In particular, our results suggest that portfolio debt, which has dominated the external liability stocks of most emerging markets until recently, is not conducive to risk sharing.
Keywords: 330; Internationaler Finanzmarkt; Kapitalmobilität; Globalisierung; Risiko; Allokation; Konjunkturzusammenhang; Dynamisches Gleichgewicht; Allgemeines Gleichgewicht; Welt; OECD-Staaten; Schwellenländer; Entwicklungsländer